Enhanced Accuracy in Construction Cost Estimates Using BIM - Aditya, I Komang Krisna; Triswandana, Erick; Agustini, Ni Komang Ayu (UKaRsT, 2024)
The Indonesian construction industry is experiencing rapid growth and increasing complexity. If done using conventional methods, this process often involves multiple manual stages that are prone to errors and inconsistencies thus requiring significant time and resources. Building Information Modeling (BIM) is a technology that provides solutions in the volume and cost estimation process. However, there have been few studies that verify the output of BIM with control calculations. This study aims to compare the volume and cost outputs from BIM with those from the Bill of Quantities (BoQ) by re-evaluating volumes identified as clashes and verifying the actual costs. Data on plan drawings, BoQ, and planned costs were obtained from a public service center building project with modeling conducted using Autodesk Revit and Naviswork. Manual volume calculations and actual cost data were used for comparison.  The results showed that the BIM cost estimate was highly accurate, with a minimal difference of IDR 1,249,901.21 (0.0032%) compared to the real cost. In contrast, the BoQ estimate was higher by IDR 1,022,985,135.58 (2.63%) compared to the real cost and IDR 1,024,235,036.79 (2.57%) higher than BIM. This is because in volume calculations, BIM software has proven to be more detailed and accurate in calculating the volume of all work items and is able to eliminate human error factors. The results of this study contribute to the construction industry by highlighting the significant advantages of using BIM software that can increase efficiency and reduce the risk of calculation errors.